2022
DOI: 10.1111/ffe.13753
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on triaxial creep behavior of red sandstone under different pore pressures based on ultrasonic measurement

Abstract: Creep behavior of red sandstone under different pore pressures with a high temperature and confining pressure condition is studied in this paper. Ultrasonic detection method is used to monitor the variation of S wave in the creep test. The attenuation coefficient and S-wave velocity in the creep process are analyzed. Fast Fourier transform is used to analyze the variation of amplitude in peak frequency and four main frequencies. The experimental results show that the creep deformation increases with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In order to analyze the frequency characteristics of the waveform more intuitively, it can be converted into frequency-domain spectra according to the fast Fourier transform (FFT) to analyze the frequency components and distribution characteristics. The ultrasonic frequency response can reflect the damage state inside the rock . The ultrasonic frequency-domain spectra of D-type and S-type shale under the initial state and different impact velocities are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to analyze the frequency characteristics of the waveform more intuitively, it can be converted into frequency-domain spectra according to the fast Fourier transform (FFT) to analyze the frequency components and distribution characteristics. The ultrasonic frequency response can reflect the damage state inside the rock . The ultrasonic frequency-domain spectra of D-type and S-type shale under the initial state and different impact velocities are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The ultrasonic frequency response can reflect the damage state inside the rock. 45 The ultrasonic frequency-domain spectra of D-type and S-type shale under the initial state and different impact velocities are shown in Figure 5.…”
Section: Time-domain Spectramentioning
confidence: 99%
“…Most of the rocks in engineering are under triaxial restricted status, especially in deeper rock masses. 48 The laboratory triaxial test plays a key role in inquiring into the failure behaviors and mechanisms for rocks, 49 and it is usually employed to determine the compression strength of rocks under different confining stresses. This study was conducted based on a triaxial compression test under isotropic confining stress conditions, which is applicable to the special case of a triaxial stress state, i.e., σ 2 = σ 3 .…”
Section: Triaxial Test and Regression Analysis 21 | Triaxial Mechanic...mentioning
confidence: 99%
“…Most of the rocks in engineering are under triaxial restricted status, especially in deeper rock masses 48 . The laboratory triaxial test plays a key role in inquiring into the failure behaviors and mechanisms for rocks, 49 and it is usually employed to determine the compression strength of rocks under different confining stresses.…”
Section: Triaxial Test and Regression Analysismentioning
confidence: 99%
“…However, when testing the initial ultrasonic velocity of the specimens, it was found that there were differences in the ultrasonic data obtained, even for the same type of specimen. Therefore, to facilitate the analysis of ultrasonic variation, the ultrasonic velocity was normalized [34,35]. The normalized ultrasonic velocity is defined as V ijB , and the ultrasonic velocity obtained from the nth wet and dry cycle of specimen number j in group i during the wet and dry cycle test is Vij(n).…”
Section: Change Rule Of Ultrasonic Velocity In Red Sandstone Specimensmentioning
confidence: 99%